Bone repair process in defects of diabetic rats filled with autogenous bone graft and covered with homogenous bone matrix membrane or polytetrafluoroethylene membrane - Timóteo, Carlos Alberto [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Shinohara, Elio Hitoshi [UNESP]; Coléte, Juliana Zorzi [UNESP] (Quintessence Publishing, 2017)
Purpose: To analyze the process of repair of bone defects in diabetic rats filled with autogenous bone and covered with membranes of homogenous bone matrix or expanded polytetrafluoroethylene (ePTFE). Materials and Methods: One hundred twenty male rats were divided into two groups: group 1 (IC), without systemic alterations (control), received an intravenous injection of citrate buffer at 0.01 M, pH 4.5; group 2 (IID) (diabetic) received an intravenous injection of streptozotocin (Sigma-Aldrich) dissolved in 0.01 M citrate buffer (pH 4.5) at a concentration of 35 mg/kg. After glycemic control was achieved, the rats were subdivided into three groups: SM (surgical cavity of the left tibia filled with autogenous bone graft, not covered by membrane); MH (surgical cavity filled with autogenous bone graft and covered with homogenous membrane); and MX (surgical cavity filled with autogenous bone graft and covered with synthetic ePTFE membrane). At 10 and 60 days, the defects in the tibiae were analyzed histologically and histometrically. Results: At 10 days, no statistically significant differences were found between the groups. However, the bone tissue of the diabetic group was qualitatively worse than that of the control group. At 60 days, a delay was found in the bonerepair process in wounds covered by the membranes regardless of the systemic state, but the quality of the newly formed bone in the wounds covered by the membranes was better in both groups. At 60 days, the diabetic group treated with homogenous membrane experienced less bone formation when compared with the nondiabetic group, and this difference was statistically significant. Such differences were even greater between the groups treated without the membrane (P <.01). Conclusion: The homogenous membrane exhibited excellent biocompatibility and was incorporated into the newly formed bone in later periods, both in diabetic and nondiabetic rats.
Keywords: Autologous transplantation; Bone grafting; Diabetes mellitus; Guided bone regeneration; Healing; Homologous transplantation